Assessment of binocular alignment using the three-dimensional Strabismus Photo Analyzer. Issue 1 (8th October 2011) - Yang, Hee Kyung; Han, Sang Beom; Hwang, Jeong-Min; Kim, Young Jae; Jeong, Chang Bu; Kim, Kwang Gi
Abstract : Aim: To evaluate the efficacy of the three-dimensional (3D) Strabismus Photo Analyzer for estimating binocular alignment using photographs. Methods: Thirty-two subjects with exotropia, 30 subjects with esotropia and 38 orthotropic subjects were included. Two independent ophthalmologists examined the angle of deviation using the Krimsky test and prism and alternate cover test (PCT). Full-face photographs were obtained using an 8.2-megapixel digital single-lens reflex camera, and the images were analysed using the 3D Strabismus Photo Analyzer. The images were adjusted for age-dependent ophthalmic biometry and angle κ. The main outcome measures were inter-observer variability, test‐retest reliability and correlation between the angles of deviation measured by different methods. Results: The 95% limit of agreement of inter-observer variability was ±3.5° (6.1 prism dioptres (PD)), ±3.1° (5.4 PD) and ±1.5° (2.6 PD) for the Krimsky test, PCT and the 3D Strabismus Photo Analyzer, respectively. The test‐retest reliability was ±2.8° (4.9 PD) for the 3D Strabismus Photo Analyzer versus the Krimsky test. The results of the Krimsky test and 3D Strabismus Photo Analyzer showed a strong positive correlation. Conclusions: The 3D Strabismus Photo Analyzer is a simple and reliable tool for measuring ocular deviation. It has excellent agreement with the Krimsky test and substantially improved reproducibility.